MURALS AS A WAY OF SOCIAL COMMUNICATION. COMPARISON OF THE WORLD EXPERIENCE - Колісник, О. В.; Пономарьова, Н. С. (Art and Design, 2019)
Investigation of the phenomenon of murals as a modern form of art and means of social communication, analysis of world experience in this area of communicative interactions. The research methodology includes historical and cultural studies of art, comparative methods, as well as a method of social analysis aimed at identifying the cultural contexts of muralism, which are determined by the socio-political, national and economic peculiarities of different countries of the world. The article defines the concept, specificity of the mural as a form of modern communicative art. The history of its origin is considered. A comparative analysis of murals and art of graffiti has been carried out, their distinctive and common features, functions in social interaction are outlined. The main purpose of the murals in the cities is determined, in particular, visualization of urgent social problems, tasks, aspects of everyday life aimed at social activity actualization, increase of the potential of civic awareness, responsibility among representatives of social majority, however, due to the possible scale of mass influence of agitation nature, requires the approval of designers, architects, sociologists, etc. The art of the mural of different cultures of the world, the themes of their socio-cultural narratives is explored. Scientific novelty. The analysis of the existing international experience of muralism, its sociocultural significance has been carried out; it has been determined that murals are not only an art form, but also powerful narratives of the information society, a means of communication between an artist or project customer, and a target audience, an effective tool for creating social dialogue, tastes and preferences. Practical significance. The results of the study reveal the possibility of a deeper understanding of the phenomenon of murals from the artistic standpoint of techniques, images, colors of modern street art, as well as a bright interactive narrative of postmodern society, in which information and communication occupy leading.